Overview of Fifth Generation Mobile Communications (International Journal of Engineering and Computer Science, 2013)
This paper explores future mobile systems with emphasis on re -configurability based on cognitive and software defined radios, 5G (fifth generation) Network architecture consisting of reconfigurable terminal able to autonomously operate in different heterogeneous access network is proposed. The proposed network is enforced by nanotechnology, cloud computing and based on all IP Platform. The paper highlights 5G main development challenges and illustrates why there is a need for 5G. New standard releases beyond 4G are in progress by standardisation bodies , but at this time are not considered as new mobile generations since implementation and rollout of systems complaint with 4G is still on the way; the goals of a 5G based telecommunications network would ideally answer the challenges that a 4G model would present once it has entered widespread use